Derivatives : markets, valuation, and risk management - Whaley, Robert E. (Robert Edward), 1953- (The Wiley finance series., 2006)
Robert Whaley has more than twenty-five years of experience in the world of finance, and with this book he shares his hard-won knowledge in the field of derivatives with you. Divided into ten information-packed parts, Derivatives shows you how this financial tool can be used in practice to create risk management, valuation, and investment solutions that are appropriate for a variety of market situations. Note: CD-ROM/DVD and other supplementary materials are not included as part of eBook file.